Pengaruh Current Ratio, Debt to Asset Ratio, Institusional Ownership dan Firm Size terhadap Return On Asset (Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017 – 2023) - Widiyanti, Eni Retno; Syarif, Devyanthi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine the effect of Current Ratio, Debt to Asset Ratio, Institutional Ownership, and Firm Size on Return on Assets in the Food and Beverage Manufacturing Subsector Companies listed on the Indonesia Stock Exchange for the period 2017-2023. The research method used is the quantitative method with a descriptive and verificative approach. The data used is secondary data, collected through quantitative data in the form of financial statements (annual report) obtained from the annual reports of Manufacturing Companies in the Food and Beverage Subsector listed on the Indonesia Stock Exchange for the period 2017-2023. Partial research results showed that the Current Ratio, Debt To Asset Ratio, and Firm Size do not have an effect on Return on Asset. Meanwhile, the results of the simultaneous test showed that the Current Ratio, Debt To Asset Ratio, Institutional Ownership, and Firm Size simultaneously affect the Return on Asset.